2015
DOI: 10.3233/bme-151517
|View full text |Cite
|
Sign up to set email alerts
|

Milkvetch root improves immune function in patients with acute exacerbation of COPD

Abstract: Abstract. Milkvetch root as a medicine has been used for more over 2000 years in China, can strengthen immune function, protect liver, promote urination, resist aging and stress, reduce blood pressure and extensively resist bacterium. This study explored the effects of milkvetch root on the immune function of patients with a definitive diagnosis of acute exacerbation of chronic obstructive pulmonary disease (COPD). The patients were randomly assigned to either the experimental or control group. All patients re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 33 publications
0
1
0
Order By: Relevance
“…The results showed that amygdalin could inhibit smoking-induced epithelial-mesenchymal transition in vivo and in vitro, and inhibit the expression of TGF-β1 [7]. In addition, patients with COPD after 14 days of milkvetch root treatment, serum TNF-α and inflammatory factor levels decreased significantly, and the proliferation and activation of immune cells were promoted [8]. The above results showed that medicinal plants played a significant role in the treatment of COPD and laid a foundation for the future research.…”
Section: Chronic Obstructive Pulmonary Diseasementioning
confidence: 95%
“…The results showed that amygdalin could inhibit smoking-induced epithelial-mesenchymal transition in vivo and in vitro, and inhibit the expression of TGF-β1 [7]. In addition, patients with COPD after 14 days of milkvetch root treatment, serum TNF-α and inflammatory factor levels decreased significantly, and the proliferation and activation of immune cells were promoted [8]. The above results showed that medicinal plants played a significant role in the treatment of COPD and laid a foundation for the future research.…”
Section: Chronic Obstructive Pulmonary Diseasementioning
confidence: 95%